2012
DOI: 10.1007/s00221-012-3096-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on ultrasonic vocalizations and laryngeal sensorimotor neurons in rats

Abstract: While decline in vocal quality is prevalent in an aging population, the underlying neurobiological mechanisms contributing to age-related dysphonia are unknown and difficult to study in humans. Development of an animal model appears critical for investigating this issue. Using an established aging rat model, we evaluated if 50-kHz ultrasonic vocalizations in 10, 32-month-old (old) Fischer 344/Brown Norway rats differed from those in 10, 9-month-old (young adult) rats. The retrograde tracer, Cholera Toxin β, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 67 publications
6
47
0
Order By: Relevance
“…Our findings were similar to age-related changes reported in previous studies examining aging rat vocalizations (Basken, et al, 2012,Johnson, et al, 2013), including reduced number of calls, increased duration, and decreased intensity in old versus young adult groups. In the Basken study, these age-related behavioral changes were correlated with significant motor neuron loss in the NA (Basken, et al, 2012). While motor neuron count in the NA was not examined in our study, it is possible that loss of NA motor neurons contributed to age-related behavioral decrements in the USVs observed to a greater extent than neurotrophin concentration.…”
Section: 4 Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings were similar to age-related changes reported in previous studies examining aging rat vocalizations (Basken, et al, 2012,Johnson, et al, 2013), including reduced number of calls, increased duration, and decreased intensity in old versus young adult groups. In the Basken study, these age-related behavioral changes were correlated with significant motor neuron loss in the NA (Basken, et al, 2012). While motor neuron count in the NA was not examined in our study, it is possible that loss of NA motor neurons contributed to age-related behavioral decrements in the USVs observed to a greater extent than neurotrophin concentration.…”
Section: 4 Discussionsupporting
confidence: 91%
“…Research in our laboratory has demonstrated that aging results in degenerative changes to the nucleus ambiguus (NA), hypoglossal nucleus (HN), and muscles involved in voice and swallowing (Basken, et al, 2012,Hodges, et al, 2004,Ota, et al, 2005,Schaser, et al, 2011,Schwarz, et al, 2009,Suzuki, et al, 2002) and that 8 weeks of tongue exercise leads to increased tongue forces across the lifespan in a rat model (Behan, et al, 2012,Connor, et al, 2009,Schaser, et al, 2012). In addition, our research suggests that brain derived neurotrophic factor (BDNF) and its receptor TrkB are a putative mechanism underlying age and exercise related change in tongue function, because the HN showed decreased TrkB with age and increased BDNF with exercise in adult rats (Schaser, et al, 2012).…”
Section: 1 Introductionmentioning
confidence: 99%
“…To determine the effect of α-syn accumulation on a rat’s vocal ability, USVs from male rats were evoked using a sexual motivation paradigm [34, 35]. In this paradigm, each male was paired with a receptive female rat (in estrous) for several days until reliable sexual interest (sniffing, chasing, and mounting) was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Avisoft-SASlab Pro software (Avisoft Bioacoustics, Germany) was utilized to analyze acoustic parameters as previously described [34]. Briefly, spectrograms were generated under a 512 FFT (fast fourier transform) length and 75% overlap frame setup.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation